THE ROLE OF PHRASES IN LANGUAGE CULTURE AND RICHNESS - Qurbonaliyeva Sabohat Ulug‘bek qizi (Journal Park Publishing, 2024)
This article examines the role of phraseology in linguistics, its importance in representing popular culture through fixed expressions, and its role in providing semantic richness in language. The types of phraseological units and their peculiarities as means of expression are analyzed, and cultural experiences are also taken into account.
Keywords: Phraseology, fixed phrases, phraseological units, semantic meaning, idioms, parables, proverbs.